سيميائية الألوان في كاريكاتير الإسرائيلي "יונתן וקסמן يونتان فكسمان" - علي، شروق محمد عبدالحميد; أبو زيد، إيمان رمزي Abu Zaid, Iman Ramzi; القاضى، ريهام محمد كمال Alqadi, Reham Mohammed Kamal (جامعة الأزهر - کلیة اللغة العربیة بالمنوفیة, 2023)
تتطرق الدراسة إلى أحد أهم عناصر التعبير الرئيسة داخل التصميم الكاريكاتيري، وهو عنصر الألوان الذى يرتبط بعملية الإدراك والتفكير وتحديد الانفعالات بالإضافة إلى الاهتمام بالجانب الثقافي وعلاقته بالأشكال المجاورة له داخل التصميم الكاريكاتيري، وذلك من خلال تحليل دلالة الألوان. تتناول الدراسة أعمال رسام الكاريكاتير الإسرائيلي " ונתן וקסמן يوناتان فکسمان" في الصحيفة الاقتصادية (כלכליסט كالكاليست)، ويتناول المحور الأول التعريف بالرسام " וקסמן فكسمان" من حيث محل ميلاده، ودراسته وأهم الجوائز التي حصل عليها خلال مسيرته المهنية في صحيفة (כלכליסט کالکالیست) الاقتصادية، بالإضافة إلى عرض موجز عن طبيعة الصحيفة وجمهورها المستهدف، وتحديدا دراسة العلامة غير اللغوية داخل وسطها الاجتماعي من خلال علم (Semiotic سيميوطيقا)، كما تعرض الدراسة تحليل ألوان أحد النماذج الكاريكاتيرية بتاريخ 8/9/2019، وتقدم الدراسة عرض السيميائية غير اللغوية والأحداث التي يدور حولها موضوع النموذج المختار مع تعريف لفظة اللون لغة واصطلاحا، ومحددات الألوان فزيائيا، ومن ثم التطبيق والتحليل السيميائي للألوان من خلال النموذج الكاريكاتيري. تحلل الدراسة الألوان التي تُمثل أحد عناصر (Semiotic سيميوطيقا) التواصل من خلال الاستدلال المنطقي، وتحدد النظام اللوني للنموذج الكاريكاتيري، وتميز كنه كل لون من الألوان داخل النموذج، وتحدد كل درجة لونية من خلال المنظور الفزيائي لها وآلية تشكيلها، كما تعرض - أيضا - محددات العلامة اللونية في معادلة تتشكل مما يأتي: (الماثول و الموضوع والمؤول والعملية التي تنظم معرفة العلامة في صورتها الذهنية)، وهم يمثلون أساس العلامة السيميوطيقية، وتحدد الدراسة الخلفية الثقافية للنموذج أو بمعنى آخر الأحداث السياسية التي تناولها النموذج الكاريكاتيري، ودلالة كل لون عند الجمهور الإسرائيلي المستهدف، كما تعرض الدراسة دلالات الألوان في العهد القديم، وآلية استخدامها في النموذج، وتحدد دلالة استخدام كل لون في موقعه داخل النموذج. The study examines one of the most important elements of expression within the caricature design, which is the colors that are related to the process of perception, thinking and identifying emotions, in addition to paying attention to the cultural aspect and its relationship to the neighboring forms within the caricature design, through analyzing the significance of colors. The study examines works of Israeli caricaturist "Yonatan Wachsman", in the economic online newspaper (כלכליסט  Calcalist), First Theme is introducing the life of the caricaturist "Yonatan Wachsman" in terms of his place of birth, his studies and the most important awards he received during his career in the economic online newspaper (כלכליסט  Calcalist), in addition to a brief presentation about the online newspaper and its customer segment. The study specifically examines the of the non- linguistic sign within its social environment through the science of (semiotics), The study also presents an analysis of the colors of one of the caricature designs on 8/9/2019, The study also examines non-linguistic semiotics and the events around which the theme of the chosen model revolves and its story, with the definition of the word color linguistically and idiomatically, and the determinants of colors physically, and then the semiotic analysis of colors through the caricature design. The study analyzes the colors that represent one of elements of communication semiotics through logical inference, defines the color system of the caricature design, distinguishes the hue of each color, and defines each color tone through its physical perspective and its formation mechanism, the study also presents determinants of color sign in an equation consisting of the following: repesentamen, object, interprentant and the process that organizes knowledge of the sign in its mental image, they represent the basis of the semiotic sign. The study identifies the cultural background of the design, or in other words, the political events dealt with by the caricature design, and the significance of each color for the segment Israeli audience, the study also presents the meanings of colors in the Old Testament, and the mechanism of their use in the design, and determines the significance of the use of each color in its location within the design.
Keywords: فن الكاريكاتير -- الرسوم الساخرة -- فكسمان، يونتان -- الكاريكاتير السياسي